Impact of school consolidation on enrolment and achievement: Evidence from India - Vinitha Varghese (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
I study the impact of school consolidation on enrolment and achievement, using its staggered roll-out in the Indian state of Rajasthan. Across the years 2014, 2016, and 2017, Rajasthan merged many of its grade 1-5 schools with grade 6-10 schools to create grade 1-10 'model' schools. Twenty-three per cent of government schools were eliminated in this education reform. Media reports suggested that consolidation led to declining enrolment levels and teacher lay-offs. Combining the government orders on consolidation and administrative data on schools, I rule-out that consolidation had a negative impact on enrolment or number of teachers. I find that consolidation decreased the number of schools in a village by one, increased the proportion of children studying in a school with a principal by 0.1, and increased the number of teachers in a village by 0.7. I also find that consolidation increased school enrolment in a village by 2 per cent- in particular, girls' enrolment increased by 2 per cent. I further show that consolidation decreased the proportion of high scorers among grade 5 students by 0.08 and did not decrease the proportion of high scorers among grade 8 students by more than 0.02. School consolidation is a policy worth pursuing in contexts that are concerned about a large number of schools.
Keywords: I24; I25; I28; I38; 330; consolidation; children; education; enrolment; schools